2019
DOI: 10.1016/j.jtumed.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of foot position on lower extremity kinematics during single leg squat among adolescent male athletes

Abstract: Objectives The purpose of this study was to investigate the effect of transverse plane foot position on lower limb kinematics during a single leg squat. Methods This was a cross-sectional study conducted among highly-trained male athletes. Only participants who showed normal knee valgus during a drop landing screening test were recruited. Twelve junior athletes performed single leg squats while maintaining a knee flexion angle of 60°. The squats were executed in three f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Moreover, fitness level and gender of participants may influence the outcomes of intervention. For instance, in a study by Mohd Azhar et al (2019) , no association was observed between foot positions and lower limb kinematics during single leg squat (i.e., bottom-up kinetic chain) among highly trained male youth athletes, although Ishida et al (2014) found significant association of similar variables among sedentary females.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, fitness level and gender of participants may influence the outcomes of intervention. For instance, in a study by Mohd Azhar et al (2019) , no association was observed between foot positions and lower limb kinematics during single leg squat (i.e., bottom-up kinetic chain) among highly trained male youth athletes, although Ishida et al (2014) found significant association of similar variables among sedentary females.…”
Section: Discussionmentioning
confidence: 95%
“…Secondly, although we ensured that the participants maintained their foot position during WBLT, the foot posture (i.e., pronation and supination) was not quantified. It was also shown that foot position did not influence knee kinematics during single leg squats among male athletes with normal DKV [33]. Future studies are recommended to investigate the relationship between foot structure (i.e., posture and arch) and landing mechanics.…”
Section: Discussionmentioning
confidence: 95%
“…The findings of the current study may be limited to the studied population. Three-dimensional analysis of SLS may provide more insights regarding lower limb biomechanics during this motion (Mohd Azhar et al 2019). Additionally, analysis on muscle synergies during SLS may elucidate the coordination and motor control involved during the motion (Shaharudin et al 2014).…”
Section: Resultsmentioning
confidence: 99%